DEVELOPING AN INTERACTIVE LANDING PAGE TO INCREASE CONSUMER BUYING INTEREST IN VARIOUS FLAVORED RICE BALL PRODUCTS - Martin Hari Purwadi; Agus Aulia Primanda; Asep Wasid; Debi Irawan; Febriansyah Ramadhan (RADJA PUBLIKA, 2025)
The development of digital technology has changed people's consumption patterns, including in making decisions to purchase fast food. This study aims to analyze how the development of interactive landing pages can increase consumer interest in buying rice balls with various flavors. Using quantitative research methods and experimental design approaches, two versions of the landing page were tested: static and interactive. The results show that interactive elements such as product animation, real-time testimonials, and quick ordering features can increase user engagement and influence purchase intentions. This study provides an important contribution to the digital marketing strategy of culinary MSMEs based on websites.